Gender, race and class in the novel ‘Curved Station’ by Uxue Apaolaza - Martin-Etxebeste, Jon (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
-
Keywords: literature; migration; feminism; social class; violence